The Man in the Water - Burton, David, 1987- (University of Queensland Press, 2019)
On the first day of year 10, Shaun sees a dead body. When Shaun finds a body floating in the lake of a quiet mining town in outback Queensland, he immediately reports it to the police. But when he returns to the site with the constable, the body is gone. Determined to reveal the truth, Shaun and his best friend, Will, open their own investigation. But what they discover is far more sinister than they expected, and reveals a darkness below the surface of their small town.